2020
DOI: 10.1101/2020.03.10.985127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peripheral tolerance checkpoints imposed by ubiquitous antigen expression limit antigen-specific B-cell responses under strongly immunogenic conditions

Abstract: A series of layered peripheral checkpoints maintain self-reactive B cells in an unresponsive state. Autoantibody production occurs when these checkpoints are breached, however, when and how this occurs is largely unknown. In particular, how self-reactive B cells are restrained during bystander inflammation in otherwise healthy individuals is poorly understood. A weakness has been the unavailability of methods capable of dissecting physiologically-relevant B-cell responses, without the use of an engineered B-ce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Nevertheless, a recent study by Brooks et.al . (56) observed that, in a transgenic mouse system where an otherwise-foreign Ag (hen egg lysozyme (HEL)) was expressed ubiquitously, the anti-HEL GC bore some resemblance to the anti-MOG GC in that it was not sustained, and had limited Memory B cell and Plasma Cell differentiation. Therefore, while MOG-sp.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a recent study by Brooks et.al . (56) observed that, in a transgenic mouse system where an otherwise-foreign Ag (hen egg lysozyme (HEL)) was expressed ubiquitously, the anti-HEL GC bore some resemblance to the anti-MOG GC in that it was not sustained, and had limited Memory B cell and Plasma Cell differentiation. Therefore, while MOG-sp.…”
Section: Discussionmentioning
confidence: 99%
“…5 Germinal center-derived autoantibodies represent a breakdown of tolerance mechanisms normally in place to maintain GC homeostasis. Autoreactive B cells that escape central tolerance either die following failure to receive T cell help [33][34][35][36] or adopt an IgM low state with reduced antibody secretion in the periphery, termed clonal anergy. 37,38 Accumulating evidence has suggested that these anergic B cells are recruited into GCs where they undergo clonal redemption and lose autoreactivity, 39,40 a process that if dysregulated could lead to autoantibody development and epitope spreading (Figure 1).…”
Section: T Cell Dependence Of Autoantibody Responsesmentioning
confidence: 99%
“…ELISA-Serum was harvested from blood collected by lateral tail vein sampling or cardiac puncture postmortem. OVA-specific and NP-specific IgG1 ELISA was performed as described (Brooks et al, 2020;Tan et al, 2020). Briefly, ELISA plates were coated with NP conjugates (NP1-RSA, NP25-BSA, NP10-BSA all from LGC Biosearch; NP3 OVA, NP7-OVA, NP9-OVA and NP19-OVA were conjugated in-house as described above), OVA (Sigma Aldrich), BSA (Research Products International) or HEL antigen (10μg/mL; Sigma Aldrich), samples were added, and HRP-labeled anti-IgG1 antibodies (Southern Biotech) were used to detect plate-bound IgG1.…”
Section: Pe-specific B Cellsmentioning
confidence: 99%